Selective recognition of small hydrogen bond acceptors by a calix[6]arene-based molecular container. Issue 1 (2nd January 2020) - Lavendomme, Roy; Desroches, Florent; Moerkerke, Steven; Topić, Filip; Wouters, Johan; Rissanen, Kari; Luhmer, Michel; Jabin, Ivan
ABSTRACT: Selective molecular recognition is of primary importance for applications such as sensing and separation of chemicals. This work describes the host-guest and crystallisation properties of a penta-carbamated calix[6]arene designed as a molecular container with a H-donating recognition group directed towards the heart of the cavity. As demonstrated by NMR spectroscopy and X-ray diffraction studies, this macrocyclic receptor can selectively recognise small H-bond acceptors through one or two hydrogen bonds, the guests nesting inside the polyaromatic cavity surrounded by eleven bulky tert -butyl groups. Graphical Abstract: